STEP-BY-STEP STUDIO drawing lifelike subjects. (WALTER FOSTER PUBLISHING, 2021)
With easy-to-follow, in-depth instruction from four accomplished artists, Step-by-Step Studio: Drawing Lifelike Subjects teaches beginners how to create convincing, detailed drawings in graphite pencil.